Análisis de las actitudes de los puertorriqueños hacia la inclusión de los menores refugiados en los centros educativos - Pierette Bartolomei-Torres, Pierette; Angelidou, Georgia; Aguaded-Ramírez, Eva (Comparative Cultural Studies: European and Latin American Perspectives, 2018)
The current conflict in Syria has caused millions of refugees to leave their country in search of asylum and a safe haven. Over the past two years both European and American citizens have received more than thousands of refugees, including children, accompanied by their parents or caretakers and unaccompanied. Similarly, Puerto Rico, which has been accepting refugees from closer countries for years refugees, has expressed its interest in receiving Syrian refugees. However, because of the country being an US territory, this decision lies in the North American country. According to international standards and the Convention relating to the Status of Refugees (1951), all refugee minors deserve a number of rights, among them, the right to education. The objective of this research is to measure the attitudes of Puerto Rican adults towards refugee minors and to verify if the Puerto Ricans accept the schooling of refugee minors in Puerto Rican schools. For this investigation a survey was conducted in which 140 Puerto Ricans participated by using the quantitative method. As a result, the majority of the Puerto Ricans accept the schooling of refugee children in Puerto Rican classrooms, they believe their arrival can be enriching and they respect their rights. In conclusion, the greater part of respondents has a positive attitude toward the inclusion of refugee minors in schools.